EFFECT OF SUBSTRATE TO DENSITY AND MORPHOMETRIC SEAGRASS LEAF (Thalassia hemprichii) IN NIRWANA SEA WATERS OF PADANG WEST SUMATERA - Nova Esterlita; Sofyan Husein Siregar; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research has been held on March-April 2018 in Nirwana sea waters of Padang. The purpose of this study was to determine the density of species, morphometrics of Thallassia hemprichii leaves. The study was also aimed to analyze the influence of substrate type on density and morphometrics of seagrass leaves. The stations were determined by purposive sampling and use transect line method for taken sample. The results of this study showed the highest density was found in Station I that has the type of substrate is coral fraction with value about 302.56 stands / m2 and thelowest density was found in Station III that has sand substrate with value 45.78 stands / m2. The longest morphometric length of the longest seagrass leaves in Station I is about 18.36 cm and the shortest at Station III with the value 7.96 cm. The morphometric average width of the widest seagrass leaves is at Station I with the value 1.2 cm and the shortest in Station III with value 0.62 cm. The result of simple linear regression test for the influence of the substrate on seagrass density and morphometric leaf with R2 value (coefficient of determination) = 0.21; 0.33; 0.16 indicates that the type of substrate affects the density and morphometrics seagrass T. hemprichii leaves. Keywords: Substrate, Seagrass , Density, Morphometric